The Peran Intervensi Gizi Sensitif (Program Kesehatan Lingkungan, Masalah Kemiskinan dan Pemberdayaan Perempuan) dalam Perbaikan Masalah Gizi Balita Stunting di Kelurahan Landasan Ulin Utara - Yudistira, Sigit; Suryani, Nany; Mubarak, Jamil; Subagus, Ahmad Yani; Aulia, Rabiatul; Jannah, Raudatul; Halidah, Halidah; Amin, M. Alief Faisal (Jurnal Kesehatan Indonesia, 2023)
Stunting is defined as a state of short or very short stature caused by linear growth that fails to reach its proper genetic potential. Stunting affects brain growth and development. Stunted children also have a higher risk of suffering from chronic diseases in their adult years. Stunting reduction requires integrated interventions, including specific nutrition interventions and sensitive nutrition interventions. This study aims to identify sensitive nutritional interventions (environmental health programs, poverty issues and women's empowerment) in overcoming the nutritional problem of stunting toddlers. This type of research is qualitative which is analyzed descriptively and in-depth interviews and observations with research samples are informants from the non-health sector, namely village heads, RW heads, RT heads, PKK. The sampling technique was carried out by purposive sampling technique. This research was conducted in the Village of Landasan Ulin Utara, Banjarbaru City. The results showed sensitive nutritional interventions for environmental health (clean Saturday or Sunday program, mutual cooperation, and eco engine training), poverty issues (keluarga harapan program, provision of BST, BLT BBM, KIS, BPJS, PNPM, and business equipment assistance), and women's empowerment (DASHAT program, MSME training, seed and livestock assistance). Sensitive nutritional interventions can be carried out on an ongoing basis and combined with specific nutritional interventions in handling stunting toddler nutritional problems.